Ballast degradation: Effect of particle size and shape using Los Angeles Abrasion test and image analysis. (30th April 2018) - Guo, Yunlong; Markine, Valeri; Song, Jianing; Jing, Guoqing
Highlights: Using laser-based technique to evaluate ballast shape characteristics. Degradation analysis of individual ballast particle based on 3-D images. Quantified assessment of ballast degradation based on 3-D image. Influence of ballast morphology (particle size and shape) on ballast degradation. Abstract: Ballast track is the most widely used track for the railway transport, and ballast bed plays a significant role to provide resistances during train operation. Generally, the ballast bed consists of crushed stones. To achieve the mitigation of ballast degradation, the first priority is to describe the degradation development and to study its effect factors. The influence of ballast morphology (particle size and shape) on ballast degradation is examined here using the Los Angeles Abrasion (LAA) test in combination with 3-D image analysis. LAA tests are used to obtain the deteriorated ballast. Then, based on the 3-D images, the changes of ballast particles after the tests were analysed. To quantify the ballast degradation (abrasion and breakage), the Abrasion Depth based on the analysis of 3-D images were proposed, while ballast breakage was estimated using the broken particles ratio. The results have shown that ballast degradation is directly related to the ballast morphology. The proposed image-based procedure can effectively be applied to assess ballast degradation. The results can be used for ballast material standardization, modelling of ballast degradation process and maintenance cycle prediction.